DUKUNGAN SOSIAL TERHADAP KONSUMSI ARV IBU RUMAH TANGGA PENDERITA HIV DI SURABAYA - Nurina Dewi Ayu Dewi; Ira Nurmala (Universitas Airlangga, 2016)
In 2014, East Java ranks second highest HIV cases in Indonesia to 32.872 the number of HIV cases. Concern HIV disease is exposed when in 2014 based on the sequence of work housewife ranks second HIV cases in Surabaya with the number of 129 cases. The case of a housewife who has HIV is higher compared to commercial sex workers. Therapeutic treatment for patients with HIV using antiretroviral drugs. ARV consumption serves to suppress the growth of HIV. This study was conducted to determine the social support for the consumptionof ARV housewife in Surabaya. The research is a qualitative research with case study approach. Informants used are numbered 9 consisting of three housewives with HIV, three families and three close friends housewife with HIV. The study was conducted from May to December 2016. Data collection using an interview guide and study documents. The results showed that there is social support for the consumption of housewives with HIV. Their diff erences in background,control beliefs, perceived behavioral control, intention-owned and social support received informants could aff ect the consumption of ARVs do informant. The conclusion that can be drawn is that the most infl uential social support for the consumption of ARV housewife with HIV in Surabaya is emotional support and support networks. Another eff ect of ARV consumption comes from a background that was once owned by housewives with HIV.Keywords: social support, consumption of ARV, housewife, HI